ATP binding cassette transporters ABCG1 and ABCG16 affect reproductive development via auxin signalling in Arabidopsis. (17th February 2020) - Liu, Liping; Zhao, Lihua; Chen, Piaojuan; Cai, Hanyang; Hou, Zhimin; Jin, Xingyue; Aslam, Mohammad; Chai, Mengnan; Lai, Linyi; He, Qing; Liu, Yanhui; Huang, Xiaoyi; et al.
Summary: Angiosperm reproductive development is a complex event that includes floral organ development, male and female gametophyte formation and interaction between the male and female reproductive organs for successful fertilization. Previous studies have revealed the redundant function of ATP binding cassette subfamily G (ABCG) transporters ABCG1 and ABCG16 in pollen development, but whether they are involved in other reproductive processes is unknown. Here we show that ABCG1 and ABCG16 were not only expressed in anthers and stamen filaments but also enriched in pistil tissues, including the stigma, style, transmitting tract and ovule. We further demonstrated that pistil‐expressed ABCG1 and ABCG16 promoted rapid pollen tube growth through their effects on auxin distribution and auxin flow in the pistil. Moreover, disrupted auxin homeostasis in stamen filaments was associated with defective filament elongation. Our work reveals the key functions of ABCG1 and ABCG16 in reproductive development and provides clues for identifying ABCG1 and ABCG16 substrates in Arabidopsis. Significance Statement: Our analyses indicate that pistil‐expressed ABCG1 and ABCG16 promote pollen tube growth, and we demonstrate that the retarded pollen tube growth in abcg1 abcg16 double mutant pistils was associated with reduced auxin distribution and auxin flow. Critically, the pollen tube growth defect observed in abcg1 abcg16 pistils was partially rescued by application of exogenous auxin. These findings also provide clues that may help identify ABCG1 and ABCG16 substrates in Arabidopsis.